Study of electrolytes magnesium electrolyzers refining of titanium impurities - Бачурский, Денис Васильевич (Technology audit and production reserves, 2012)
This article describes the results of the study the degree of influence of the partial-pressure of water above the melt, the melt temperature and the concentration of magnesium chloride on the deposition of Reed particles containing titanium in electrolytes magnetic pots